Maskulinitas Partai Nasional Demokrat Dalam Penentuan Udeng Dara Kepak Sebagai Simbol Perjuangan Di Bali - Supriyanti, Ni Made Inten; Bandiyah, Bandiyah; Ali Azhar, Muhammad (Jurnal Nawala Politika, 2018)
ABSTRACT Patriarchal culture tends to be one of the factors causing less favorable treatment for women. Patriarchy is a system of social structures where men dominate women. In the case of determining Udeng Dara Kepak at the Bali Democratic National Party Regional Leadership Council, women were impressed only by following the order made by men. As a research frame, the theory used in this study is the theory of female existentialism. The method used in this study is descriptive qualitative. Based on the data analysis carried out, the findings were obtained that, first, political parties only fulfilled the policy of affirming women's quota as a form of formality so that the existence of women became the object of male construction only. Secondly, masculinity in political parties is formed as a result of the shackles of patriarchal culture inherent in women in Bali and the assumption of women being complementary is legitimized by the existence of cultural products in the form of Udeng Dara Kepak as a political symbol that favors men only. Based on these findings, it was concluded that the determination of Udeng Dara Kepak as a symbol of struggle is one form of gender bias in the viewpoint of the chairman of the Bali Democratic National Party Regional Leadership Council as a "decision maker". Keywords: Patriarchy, Women, Udeng Dara Kepak